The Impact of Rumors on Public Opinion - Al-Hamdani, Nisreen Yassin (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to identify the impact of rumour on public opinion. In order to achieve this objective, the study discussed the concept of rumour, its characteristics, types, objectives, motives, stages of formation and conditions of success. The study also discussed the concept of public opinion, its characteristics, functions and composition, The study used the behavioural methodology.The study reviwed number of studies that investigated this relationship. The study revealed that there is a significant impact of rumour in terms of its ability to transform the concepts and direction of public opinion to achieve its goals.